2022
DOI: 10.1055/a-1903-2226
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Purification, Quantification, and Stability of Bioactive Spilanthol from Acmella oleracea

Abstract: Acmella oleracea is an ethnobotanically significant plant with a relatiwely high content of spilanthol. Due to its broad spectrum of activity, including anti-inflammatory, antioxidant, analgesic, antifungal, and bacteriostatic properties, it is considered a valuable bioactive natural product. In addition, spilanthol as its main bioactive component inhibits facial muscle contractions, making it an attractive ingredient in anti-wrinkle and anti-aging cosmetics. Due to its muscle paralyzing effects, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…There has been increasing interest in NP drug discovery ( 1 ), new nutrition sources from plant diversity ( 49 ), and the exploration of beneficiary effects of herbs ( 50 ). These extensive investigations are generating data on a wider variety of NP activity ( 51 , 52 ) and on the composition/concentration of NPs in various species ( 53 , 54 ). The rich information generated from these and future investigations can be incorporated into the NPASS database and other established databases ( https://data.nal.usda.gov/dataset/usda-database-flavonoid-content-selected-foods-release-32-november-2015 ) ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…There has been increasing interest in NP drug discovery ( 1 ), new nutrition sources from plant diversity ( 49 ), and the exploration of beneficiary effects of herbs ( 50 ). These extensive investigations are generating data on a wider variety of NP activity ( 51 , 52 ) and on the composition/concentration of NPs in various species ( 53 , 54 ). The rich information generated from these and future investigations can be incorporated into the NPASS database and other established databases ( https://data.nal.usda.gov/dataset/usda-database-flavonoid-content-selected-foods-release-32-november-2015 ) ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they can be used for the pretreatment of plant material, which facilitates subsequent extraction [140]. However, traditional isolation methods, such as maceration or extraction in Soxhlet's apparatus, are still often employed as effective techniques for isolation of plant ingredients, especially those mentioned in this work [141][142][143][144]. Table 6 presents the review of extraction methods of active chemicals from A. oleracea, C. asiatica, P. corylifolia, P. lanceolata, and S. virgaurea.…”
Section: The Most Important Applications Of a Oleracea C Asiatica P C...mentioning
confidence: 99%
“…It contains several bioactive compounds, including spilanthol, used commercially as an anti-inflammatory, for mouth and throat treatments and as an anesthetic (Rondanelli et al 2020). Additionally, Grymel et al (2022) reported that spilanthol inhibits subcutaneous muscle contraction, enabling its application in cosmetics.…”
Section: Sombreamento E éPoca De Cultivo No Desempenho Agronômico De ...mentioning
confidence: 99%